A role of radioprotective agents in cancer therapeutics: a review - Velpula, Nagalaxmi; Ugrappa, Sridevi; Kodangal, Srikanth (International Journal of Basic & Clinical Pharmacology, 2017)
In the field of medicine or dentistry, cancer is one of the most common causes for death of the individual worldwide, in which oral cancer accounts for about 10% of it. One of the most important treatment modalities for cancer includes radiotherapy. During radiotherapy, exposure of the normal tissue to these ionizing radiations, results in mutagenesis and cell death. Several modalities and clinical approaches have been made to reduce these early and late complications of the radiotherapies and one among them is, by the means of pharmacological agents. Many experimental and clinical studies have given rise to new concepts of chemical and molecular pharmacological agents that could be effective in protection and treatment of radiation damage to surrounding normal tissues. Clinical Significance: To reduce the significant complications in irradiated patients, the clinical implication of these radioprotective agents have emerged as potential drugs and with anti-tumour effect in the radiotherapy of various cancers including oral carcinomas.